(untitled) (Bangladesh Journal of Nutrition, 2018)
Child and maternal malnutrition is a major public health problem in Bangladesh. The study assessed children and pregnant women malnutrition, and pregnancy weight gain in urban poor areas of Dhaka and Chittagong City, Bangladesh. This longitudinal study analyzed data of children <2 years and pregnant women using growth monitoring and promotion (GMP) cards. A total of 4223 GMP cards of urban static and satellite clinics were included in this study. The study found that the prevalence of low birth weight (LBW) was about 15% and that underweight was about 25%; male children were significantly more underweight than the female children. Underweight was high among children aged 18-23 months followed by ><6 months. More than one third of the pregnant women (36.4%) suffered from malnutrition (BMI><18.5) at their first trimester. Overall, 23% of the pregnant women were malnourished based on mid upper arm circumference (MUAC) ><21.5 cm, irrespective of their pregnancy status. Median pregnancy weight gain was 7.0 kg. Almost two-third of the pregnant women (63.6%) failed to gain desired weight (>4 kg) during the third trimester. Overall, 35.4% of pregnant women conducted 3 or more antenatal care visits throughout her pregnancy period. Prevalence of child and maternal malnutrition was significantly high in urban poor areas of Dhaka than those in Chittagong areas. Lack of continued participation in GMP program is a great challenge. Nutrition intervention programs should be intensified in the urban poor areas to address maternal and child nutrition problems. Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 73-80